Tindak Tutur Direktif dalam Novel Azzamine Karya Sophie Aulia - Shelsa Alya Yosta; Ermanto (Universitas Negeri Padang, 2024)
This study aims to describe: (1) the types of directive speech acts in the novel Azzamine by Sophie Aulia. (2) the strategy of directive speech action in the novel Azzamine by Sophie Aulia. (3) the function of directive speech in the novel Azzamine by Sophie Aulia. The object of this research is Sophie Aulia's novel Azzamine which was published in 2022.